An unusual epithelial pleomorphic giant cell tumour of the pancreas with osteoclast-type cells. - Martin, A (1994)
A case of giant cell tumour of the pancreas with a mixture of pleomorphic giant cells and osteoclast-like cells is described. This association is rare and its histogenesis has been debated. The presence of a small differentiated adenocarcinomatous area at the periphery of the tumour indicates an epithelial origin. Moreover, some pleomorphic cells were positive for keratin (KL1). The osteoclast-like cells strongly expressed CD68 (a marker of histiomonocytic lineage) and did not show proliferative activity. They probably correspond to an unusual reaction of the stroma. Their clinical importance in this type of tumour remains unknown.